Design and fabrication of vapor-induced superhydrophobic surfaces obtained from polyethylene wax and silica nanoparticles in hierarchical structures. Issue 44 (13th July 2018) - Guan, Yong; Yu, Chenchen; Zhu, Jiawen; Yang, Rui; Li, Xiang; Wei, Dafu; Xu, Xiang
Abstract : Fabrication of superhydrophobic surfaces based on PEW and SiO2 though a vapor-induced method. Abstract : The present work reported a simple and effective approach to fabricate a low-cost, self-cleaning and mechanically durable superhydrophobic coating. The coating was prepared by dip-coating certain substrates in an ethyl acetate suspension of silica nanoparticles (SiO2 ), hydroxyl acrylic resin, cross-linking agent and polyethylene wax (PEW). Through the control of the cooling and drying process, vapor-induced PEW micro-clusters were formed on the surfaces during the evaporation of ethyl acetate, and uniform carpet-like hierarchical structures were finally obtained by properly adjusting the dosage of PEW. Under the synergistic effect of hydrophobic SiO2 nanoparticles and PEW micro-clusters, the composite coating exhibited a remarkable superhydrophobicity with a contact angle of 163° ± 5° with 25 wt% content of PEW, as well as preeminent self-cleaning properties against various food liquids. Moreover, the coating still maintained its surface cleanliness when immersed in the cyclohexane or hexadecane, indicating a superior self-cleaning property against solvent-contamination. The mechanical durability test showed that the coating still kept its excellent water repellency after fairly intensive knife-scratching, tape peeling and 25 cycles of sandpaper abrasion under 100 g of loading, indicating a quite admirable mechanical durability. The facile preparation and high-performance of the coating make it quite suitable for manufacture on a large scale, which is favorable for the development of superhydrophobic coatings.